Numerical modeling and experimental validation of a passive solar distillation of ethanol - Silva, Isadora Barbosa; Faria, Erica Victor; Sousa, Nádia Guimarães; Santos, Kássia Graciele (Latin American Journal of Energy Research, 2024)
The increasing global demand for sustainable energy solutions highlights the potential of solar energy, a clean and abundant resource, for industrial processes such as distillation. This study investigates the passive solar distillation of ethanol mixed with a small fraction of oil, utilizing a phenomenological model validated against experimental data. Solar energy was employed to heat the mixture, capitalizing on its environmental benefits and cost-effectiveness, particularly in regions with high solar irradiation. Experiments were conducted with initial ethanol volumes of 500 mL, 750 mL, and 1000 mL, with temperature and distillate mass measured throughout the distillation process. The model accurately predicted the temperatures of the basin, ethanol, and glass cover, as well as the distillate mass, with prediction errors below 6%. Results indicate that solar radiation and wind speed significantly influence thermal efficiency, which ranged from 18.9% to 26%. It was achieved an average productivity of 4500 to 6500 mL/day·m² of distillate ethanol. The model’s accurate predictions of distillate production demonstrate its potential as a valuable tool for optimizing passive solar distillation systems.
Keywords: numerical simulation; mass transfer; renewable energy; sustainable processes; heat transfer